2020
DOI: 10.1109/tdei.2019.008342
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analysis of cellulosic insulation failures of continuously transposed conductors under short circuits and thermal ageing in power transformers

Abstract: The integrity of the cellulosic insulation in power transformers is considered one of the most relevant parameters that affects their performance and reliability. Electric faults, such as short circuits, have thermal and mechanical effects that degrade the paper and can eventually produce the end-of-life of the transformer. The evolution of the properties of the paper insulation of a commercial continuously transposed conductor due to thermal ageing was characterised through the degree of polymerisation and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(39 citation statements)
references
References 11 publications
(12 reference statements)
2
37
0
Order By: Relevance
“…The ageing temperature of 150 °C was selected for this study based on prior publications by the same authors involving diverse cellulosic materials used as insulation in transformers [8] , [9] , [10] . These earlier investigations revealed that a lower ageing temperature would have required over seven months of accelerated thermal ageing to achieve an insulation state comparable to the entire operational lifespan of an actual transformer.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The ageing temperature of 150 °C was selected for this study based on prior publications by the same authors involving diverse cellulosic materials used as insulation in transformers [8] , [9] , [10] . These earlier investigations revealed that a lower ageing temperature would have required over seven months of accelerated thermal ageing to achieve an insulation state comparable to the entire operational lifespan of an actual transformer.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Those cracks were classified according to their size, after being studied macroscopically and microscopically, through Scanning Electron Microscopy. More details about the ageing process, the bending tests and their results can be found in [4].…”
Section: Experimental Methods a Thermal Ageing And Bending Tests Over...mentioning
confidence: 99%
“…The tensile strain 𝜀 𝑡 (%) and stress 𝜎 𝑡 (𝑀𝑃𝑎) were obtained as in ( 1) and ( 2), where 𝐿 0 and 𝐿 𝑓 (𝑚𝑚) are, respectively, the initial distance between jawns and recorded elongation; 𝐹 (𝑁) is the recorded force; 𝐴 (𝑚𝑚 2 ) is the cross-sectional area of the paper strip (product of the width, 𝑤, by the thickness, 𝑡). The detailed results of tensile tests in MD and CD can be found in [4].…”
Section: Experimental Methods a Thermal Ageing And Bending Tests Over...mentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous recent studies on the influence of vegetable oils in the chemical and dielectric properties of the transformer insulation, such as [5][6][7][8][9]. Nevertheless, there are only a few which analyse their impact on the mechanical properties of the solid insulation, for instance [10,11]. Thus, it can be claimed that there is a lack of understanding about how the ageing process with vegetable oils affects the mechanical performance of the dielectric paper in transformer components such as Continuously Transposed Conductors (CTCs), especially for papers different from Kraft type, such as crepe.…”
Section: Introductionmentioning
confidence: 99%